Uji Sensori dan Formulasi Produk Bumbu Penyedap Berbasis Jamur Tiram (Studi Pengembangan Produk Alternatif Monosodium Glutamate) - Sri Kadaryati; Margaretha Arinanti; Yuni Afriani (agriTECH, 2021)
Monosodium glutamate (MSG) is used as flavour enhancer in food preparation. The regulations in Indonesia didn’t mention the maximum limit for using MSG. This resulted in the pro and contra regarding the side effects of MSG. On the other hand, complex process of fermentation, purification and crystallization were needed to make MSG. These various things led to the thought of finding alternative flavour enhancers that were relatively safer with simpler processes. The previous study has shown that oyster mushroom (Pleurotus ostreatus) was potential to be develop into a flavouring product as an alternative of MSG. Product formulations was needed to produce the accepted products by taste and economic. Sensory test was needed in the product development process to determine the panellists acceptance of the product. This study aims to provide the panellist preference for sensory tests. This study was an observational laboratory study, conducted on June 2018-April 2019, at Laboratorium Gizi/Kulinari, Universitas Respati Yogyakarta. The 1st sensory test was carried out to know the difference between the oyster mushroom-based flavouring formula and MSG, and the panelists preference level of the formula. The flavouring formula in the 2nd sensory test was made by adding a combination of sugar and salt. The 2nd phase of sensory test was carried out to find out the most acceptance formula by the panellists. Each sample was dissolved in warm water, then 30 ml for each sample was served. The basic ingredients of this formula were oyster mushroom flour which were prepared by soaking in 6.25 ppm of sodium bisulfite solution for 10 minutes, followed by cabinet drying with temperature of 50ºC for 30 hours. Formula 403 is the best flavouring formula based on sensory test results. Future studies can consider products using for food processing in the food service.